Assessment of private Sector Employees in Terms of Education in Northern Cyprus - ÖZTÜRKLER, Ziya (2021)
Nowadays, we must follow the rapid advances in technology and the implementation of competitive activities that the most important of them are educational activities. It is found that professions that do educational activities exhibit better financial performance than jobs that do not this. In this research, it is tried to specify the perceptions and views of employees of private sector companies in Northern Cyprus concerning the purpose of education, determination of training needs, implementation of education, and assessment of the education program. The objective of this study was to determine whether there is a difference in the perceptions and views of employees working in the private sector, especially in Northern Cyprus, regarding their performance and evaluation in academic fields. As a result, according to the results of the survey applied, there is a significant relationship between the importance given to education and the evaluation of the amount of education in private sector companies in northern Cyprus, for educational activities and development are essential and mandatory for employees working in companies. If the results of the training assessment used after education are reliable in the companies, the results will be also employed in the next education.